PROBLEMATIKA NIKAH SIRI DI KECAMATAN MUARA SIPONGI DALAM TINJAUAN HUKUM ISLAM DAN HUKUM NEGARA - Uswatun Hasanah (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2022)
Siri marriage problems are increasingly rampant, one of which is in Muara Sipongi District. The existence of underage couples who are married in series for reasons of age does not reach the age limit for marriage according to the regulations of the Act. As for this research, it is included in empirical (field) research. The research informants are the parties to the marriage. It is known that in Islamic law siri marriage is legal, but in the law of the country it is invalid because of the necessity for marriages to be recorded (marriage registration). However, marriage should be avoided because it will complicate their domestic affairs in the future.